Peningkatan Kreatifitas dan Efektifitas Pembelajaran Daring Matematika Bagi Guru SMP di Kecamatan Pattalassang melalui ISpring dan GeoGebra - Naimah Aris; Nur Erawaty; Irma Andriani; Jusmawati Massalesse; Kasbawati Kasbawati; Sri Astuti Thamrin; Okta Nofri; Muhammad Zakir; Sitti Sahriman (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Daring mathematics study leaves pupils with troubles and anxiety after more than a year of daring learning. Furthermore, students often struggle to understand instructional materials that need graphic interpretation when learning mathematics. This activity aims to improve the competence of mathematics teachers with skills using the iSpring and GeoGebra so that they can create creative and effective learning media so that their virtual mathematics learning becomes more interesting and understandable for students. This activity is conducted daring via Zoom and live on YouTube, as well as offline meetings that are carried out with due observance of health protocols. Lectures, demonstrations on the use of iSpring and GeoGebra, as well as monitoring and evaluation are methods used in daring and offline activities. The target audience for this community service is Middle School Mathematics teachers in Pattalassang District. The results of the training showed an increase in the understanding and skills of mathematics teachers in utilizing iSpring and GeoGebra multimedia. This improvement in IT skills can contribute to increasing creativity and effectiveness in learning mathematics in the classroom.